Influence of dietary supplementation of chromium on the carcass traits of crossbred pigs - Pamei, Guikinglung; Gnanaraj, P. Tensingh; Sivakumar, T.; Jawahar, K. Thilak Pon; Muthuramalingam, T.; Pothiappan, P. (Journal of Advanced Veterinary and Animal Research, 2014)
This study was conducted to assess the influence of chromium on the carcass traits in crossbred (Large White Yorkshire X Landrace) pigs fed with swill feeding for a period of 5 months. Early-weaned crossbred piglets (n=24) were selected for this study, and the piglets were randomly divided into three equal groups; Group I, II, and III. The piglets were reared by following standard health coverage protocols. The feeds of Group I and II were supplemented with chromium in the form of chromium tripicolinate at 0.1 and 0.2 mg/kg of swill feed respectively, and Group III was kept as control. Carcass weight, carcass length, and bone percentage showed no significant difference among the three groups. However, better dressing percentage was observed in Group I (p<0.05). Liver and kidney weights were reduced in chromium supplemented groups (p<0.05). Chromium supplemented groups showed lower backfat thickness and fat percentage (p<0.01); whereas, loin eye areas and muscle percentage were increased as compared to the control group. Thus, it was concluded that chromium supplementation in feed of crossbred piglets influenced positively in their carcass traits. DOI: http://dx.doi.org/10.5455/javar.2014.a22 J. Adv. Vet. Anim. Res., 1(3): 125-129, September 2014